2010
DOI: 10.1002/cyto.a.20929
|View full text |Cite
|
Sign up to set email alerts
|

Detection of molecular targets on the surface of CD34+CD38 bone marrow cells in myelodysplastic syndromes

Abstract: Myelodysplastic syndrome (MDS) is a kind of clonal stem-cell disorder in which aberration within a hematopoietic stem cell (HSC) gives rise to the entire disease as in acute myeloid leukemia (AML). Studies have showed that contrasting normal stem cells, AML stem cells express CD96 and CD123, but lack of CD90, although both of them reside within the CD34 1 CD38 2 population. So far, little is known about expression of the markers on MDS HSC. In this study, we analyzed the immunophenotypic characteristics of CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
(62 reference statements)
3
23
0
Order By: Relevance
“…Additional differentially expressed proteins are also listed in Supporting Information Table S1. Other studies identified aldehyde dehydrogenase activity (ALDH), B‐cell lymphoma/leukemia 11A (BCL11A), ILK, and HLA‐DR as highly expressed proteins in leukemia stem cells 28–31. These proteins were also overexpressed in CD34 + /CD38 − AML cells in the present study (Table 2), indicating an acceptable sensitivity of the current study.…”
Section: Resultssupporting
confidence: 57%
“…Additional differentially expressed proteins are also listed in Supporting Information Table S1. Other studies identified aldehyde dehydrogenase activity (ALDH), B‐cell lymphoma/leukemia 11A (BCL11A), ILK, and HLA‐DR as highly expressed proteins in leukemia stem cells 28–31. These proteins were also overexpressed in CD34 + /CD38 − AML cells in the present study (Table 2), indicating an acceptable sensitivity of the current study.…”
Section: Resultssupporting
confidence: 57%
“…In haematological malignancies, identification of cells with different growth capacities is based on cell surface antigens and these exhibit functional heterogeneity [42]. Flow cytometry is a widespread and reliable method to detect antigens on single cells [43]. We analyzed cell surface antigens on single cell suspensions derived from xenografted tumours from our colon carcinoma cell line panel.…”
Section: Discussionmentioning
confidence: 99%
“…In stem cell research in general and MSC research in specific, immunophenotyping is preferably performed by multicolor flow cytometry to simultaneously demonstrate the coexpression of specific MSC markers and the absence of hematopoietic antigen expression (7,14). However, many flow cytometric techniques have been developed for analyzing mature, nonadherent leukocytes, and therefore, some refinements are required when using stem cells (15).…”
mentioning
confidence: 99%